Transforming the publishing industry in the digital age: challenges and opportunities - Kalmykov, Alexey (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
In the digital age, the publishing industry has been subject to a tremendous revolution brought by technological advancements and changing consumer behavior. This research delves into the disruptions and new opportunities brought on by digitalization to traditional publishing workflows in content creation, content distribution, and content monetization. The emergence of digital platforms, self-publishing and subscription- based services poses a threat to traditional publishing models, fundamentally altering the process of how content is created and shared. With digitalization gaining more and more momentum, audiences get a more interactive, personalized experience and there has been a rapid rise of eBooks, audiobooks and digital subscriptions. But that transformation also has made life difficult for publishers: copyright enforcement, the competition from giant platforms money when you depend on ads. The primary objective of this research seeks to look into the challenges that publishers face in adopting to the digital ethos and the opportunities digitalization has facilitated for growth and innovation.